THE DETERMINANTS IN THE MANAGEMENT OF PREGNANCIES COMPLICATED WITH IMMUNE THROMBOCYTOPENIA - Çiğdem Kunt İşgüder; Tuğba Saraç Sivrikoz; Mehtap Akın; Mustafa Törehan Aslan; Lütfiye Uygur; Şule Birol İnce; İbrahim Kalelioğlu; Sevgi Kalayoğlu Beşışık; Recep Has; Alkan Yıldırım (İstanbul Tıp Fakültesi Dergisi)
Objective: This study aims to determine the hematologic and obstetric factors that would affect the management of immune thrombocytopenia (ITP) during pregnancy. Material and Method: This is a retrospective review of 54 pregnancies that were complicated by ITP at a single tertiary center. All of the patients were followed-up and delivered at the same center. Subgroup analysis for obstetric outcomes was made according to the platelet counts at the time of delivery (<50x103/mm3 or ≥50x103 /mm3 ), the time of diagnosis (before or during pregnancy) and neonatal platelet counts (≤100x103 /mm3 or >100x103 /mm3 ). Result: Transfusion of blood products, steroid administration per se, or in combination with intravenous immunoglobulins (IVIG), were significantly more often administered in those with platelet counts <50x103 /mm3 at the time of delivery (p=0.020, p=0.020, and p=0.004, respectively). The patients who were first diagnosed with ITP during pregnancy had higher rates of transfusion of blood products (p=0.041), higher rates of vaginal deliveries (p=0.048), and lower rates of preterm delivery (p=0.044) when compared to the patients who had ITP diagnosed before the on set of pregnancy. Gestational age at birth (p=0.020), birth weight (p=0.002) and neonatal platelet count (p=0.002) were significantly higher in those who were diagnosed during the pregnancy. History of maternal splenectomy, intensive care unit admission, IVIG administration, and blood transfusion were significantly more frequent in neonates with platelet counts ≤100x103 /mm3 (p=0.028, p=0.001, p=0.001, and p=0.025, respectively). Conclusion: The women diagnosed with ITP before the pregnancy and those who were diagnosed during the pregnancy had comparable rates of postpartum bleeding. However, there was a tendency towards overtreatment of the women who developed ITP during pregnancy.